GAMBARAN PENGETAHUAN SUAMI DARI IBU MENYUSUI (0-6 Bulan) TENTANG ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS DERMAYU KABUPATEN SELUMATAHUN 2017 - Iswari, Indra (Journal Of Midwifery, 2018)
Breastfeeding coverage in Indonesia in 2016 revealed that the percentage of infants received exclusive breastfeeding until the age of 6 months was 29.5% and breast-fed infants 0-5 months were 54.0%. The low achievement of exclusive breastfeeding programs can occur due to several obstacles, including low knowledge of exclusive breastfeeding. Knowledge of the husband plays an important role as support in the success of exclusive breastfeeding. This study aimed to determine the description of husband's knowledge of breastfeeding mothers (0-6 months) about exclusive breastfeeding in the working area of Dermayuhealth center of Seluma District in 2017. The research method used in this research was descriptive research, with 73 respondents taken by accidental sampling technique. The type of data used in this study using primary data was analyzed using univariate analysis. the results of this study indicated that almost some of the respondents (34.2%) had less knowledge about exclusive breastfeeding. To the institute of Dermayu health center, Seluma District is expected to increase the knowledge of the community about exclusive breastfeeding especially on the husbands of mothers who have babies so that the knowledge of the husband can be better in providing support to the baby.